SETTLEMENT OF SHARIA ECONOMIC LEGAL DISPUTES INDONESIA'S POSITIVE LEGAL PERSPECTIVE - Yuniartik Yuniartik (ADISAM PUBLISHER, 2023)
This study discusses sharia economic law, where currently economic growth has developed greatly in accordance with the current era, so that people also find it difficult to solve Islamic economic problems. The focus of the problem in this study is how to solve economic problems in sharia economic law from the perspective of Indonesian positive law? The purpose of this study is to find out how to solve economic problems using the classical tradition. The type of research used is library research using a juridical approach. And research results This found that in finish problem economic dispute sharia perspective Indonesia's positive law can be pursued in several ways, namely peace and Alternative Dispute Resolution (ADR) and arbitration (tahkim).